Liver Enzyme Correlated with C-Reactive Protein as a Biomarker of Metabolic Syndrome in Elderly Patients: Metabolic Syndrome Related with Liver Enzyme and CRP - Ghani, Rubina; Emad, Shaista; Perwaiz Khan, Samia; Naseeb, Uzma; Ahmed, Fahad; Zia, Sehrish (Pakistan Journal of Health Sciences, 2023)
Metabolic syndrome is a multifactorial disease with various risk factors that arise from insulin resistance associated with obesity, diabetes, hypertension, and dyslipidemias. Objective: To investigate the association between C-Reactive Protein and various risk factors related to CVS and metabolic health in elderly adults. Increased levels of various liver enzymes were found to be indicative of the progression of metabolic syndrome. Methods: In this study, total of 150 individuals with diagnosed metabolic syndrome were included, and they were compared to an equal number of control cases. The participants were selected from individuals visiting the Pathology and Molecular Biology Laboratories in Karachi for lab investigations. before collecting blood samples, basic vital signs, blood pressure, height, and waist circumference measurements were recorded to determine the participants' body mass index. The blood samples were then taken to assess liver enzyme levels and CRP. Results: The study examined and compared the levels of inflammatory marker and liver enzymes in both cases of metabolic syndrome (MetS) and the control group. The findings revealed a significant association (p-value of 0.001) between metabolic syndrome and elevated levels of liver enzymes and CRP. Specifically, the suspected cases of metabolic syndrome showed strong correlations with alanine aminotransferase, gamma-glutamyl transferase, and aspartate aminotransferase. However, alkaline phosphatase did not show substantial differences between the two groups. Conclusions: Our research revealed correlation between metabolic syndrome, liver enzymes and CRP. These findings indicate that high levels of liver enzymes and CRP can be indicative of cardiovascular functional abnormalities in elderly patients with metabolic syndrome.